2004
DOI: 10.1071/ch03231
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquids—An Overview

Abstract: Ionic liquids have become an increasingly popular class of solvent in the last decade as the potential applications of these materials become more diverse. Rather than being viewed simply as replacement for conventional organic solvent media, research into ionic liquids has progressed to the deliberate choice and design of these materials for reasons of improved rate, specificity, and yield. Design of ionic liquids centres on the development of novel cations and anions to impart the specific physical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
360
0
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 588 publications
(369 citation statements)
references
References 2 publications
4
360
0
5
Order By: Relevance
“…16 ILs are organic salts composed of anions and cations that are in the liquid state at ambient conditions and many show negligible volatility and non-flammability. 17 Hence, they are being actively investigated as alternative solvent media in synthesis, 18 catalysis, 19 polymerization, [20][21][22] separation, 23 electrochemistry 24,25 and electrochemical devices. 26,27 However, the basic science involved with fully characterizing these ILs is still in its infancy, and this may be holding back the complete and most efficient utilization of these potentially, and only in some cases, 28 41 dried under vacuum at 40 1C for 48 h, and stored under argon at 20 1C before analysis.…”
Section: Introductionmentioning
confidence: 99%
“…16 ILs are organic salts composed of anions and cations that are in the liquid state at ambient conditions and many show negligible volatility and non-flammability. 17 Hence, they are being actively investigated as alternative solvent media in synthesis, 18 catalysis, 19 polymerization, [20][21][22] separation, 23 electrochemistry 24,25 and electrochemical devices. 26,27 However, the basic science involved with fully characterizing these ILs is still in its infancy, and this may be holding back the complete and most efficient utilization of these potentially, and only in some cases, 28 41 dried under vacuum at 40 1C for 48 h, and stored under argon at 20 1C before analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Past reviews have provided detailed insight into the synthesis and properties of ILs and have promoted their implementation as common laboratory solvents. 8 non-polar functional groups to encourage specific location within the liquid domains. 9 It was found that the interactions with the ions allowed for the spiropyran moiety to be located in distinctly different regions and report on them through thermodynamic and kinetic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews have provided detailed insight into ILs and have promoted their implementation was common laboratory solvents. 6 However, the lack of exact knowledge of the physical properties has resulted in their widespread application not being completely realised. Recent studies have proposed that imidazolium based ILs may form ordered systems resembling psuedo-crystalline systems based on stacking of mutual charges (aggregation) or ordered association of cation to surrounding anions and vice versa.…”
Section: Introductionmentioning
confidence: 99%